Update on the pathology, genetics and somatic landscape of sebaceous tumours - Ferreira, Ingrid; Wiedemeyer, Katharina; Demetter, Pieter; Adams, David J.; Arends, Mark J.; Brenn, Thomas (Histopathology, 2020)
Cutaneous sebaceous neoplasms show a predilection for the head and neck area of adults and include tumours with benign behaviour, sebaceous adenoma and sebaceoma, and sebaceous carcinoma with potential for an aggressive disease course at the malignant end of the spectrum. The majority of tumours are solitary and sporadic, but a subset of tumours may be associated with Lynch syndrome, also known as hereditary non-polyposis colon cancer (HNPCC) and previously referred to as Muir-Torre syndrome (now known to be part of Lynch syndrome). This review provides an overview of the clinical and histological features of cutaneous sebaceous neoplasia with an emphasis on differentiating features and differential diagnosis. It also offers insights into the recently described molecular pathways involved in the development of sebaceous tumours and their association with Lynch syndrome.